Field evaluation of an electrostatic PM2.5 mass monitor - Panich Intra (2018)
© 2018, Prince of Songkla University. All rights reserved. An electrostatic PM2.5 mass monitor (EPMM) used for wireless continuous airborne particulate matter monitoring was developed and field evaluated in our previous work. Developed electrostatic PM2.5 mass monitor was consisted of a 2.5 impactor, a particle charger, a Faraday cup electrometer, a flow system, a high voltage power supply, and data acquisition, processing, and wireless monitor system. The monitoring data of the EPMM was connected to the internet through a GSM connection to a public cellular network. In this study, the EPMM performance was simultaneously evaluated and compared with a commercially available Thermo Scientific Model 5014i Beta Continuous Particulate Monitor for PM2.5 measurements at ambient conditions. The monitoring station was located in Yupparaj Wittayalai School, Si Phum, Mueang, Chiang Mai, Thailand, during October 15 to November 5, 2015. The two different instruments showed good results that were highly correlated. It was found that the comparison between the EPMM and the Thermo Scientific Model 5014i Beta data values were R2of 0.8230 and 0.9811, and a slope of 1.0231 and 0.8802 for 1-hour and 24-hours, respectively. Particularly, it was showed that the EPMM proved its advantages in measuring and detecting PM2.5 particulate air pollution for mass concentrations in the range from 0 to 500 µg/m3and with greater than 500 hours of operation.